Allosteric Modulation of the HIV-1 gp120-gp41 Association Site by Adjacent gp120 Variable Region 1 (V1) N-Glycans Linked to Neutralization Sensitivity - Drummer, H.; Hill, M.; Maerz, A.; Wood, S.; Ramsland, Paul; Mak, J.; Poumbourios, P. (2013)
The HIV-1 gp120-gp41 complex, which mediates viral fusion and cellular entry, undergoes rapid evolution within its external glycan shield to enable escape from neutralizing antibody (NAb). Understanding how conserved protein determinants retain functionality in the context of such evolution is important for their evaluation and exploitation as potential drug and/or vaccine targets. In this study, we examined how the conserved gp120-gp41 association site, formed by the N- and C-terminal segments of gp120 and the disulfide-bonded region (DSR) of gp41, adapts to glycan changes that are linked to neutralization sensitivity. To this end, a DSR mutant virus (K601D) with defective gp120-association was sequentially passaged in peripheral blood mononuclear cells to select suppressor mutations. We reasoned that the locations of suppressors point to structural elements that are functionally linked to the gp120-gp41 association site. In culture 1, gp120 association and viral replication was restored by loss of the conserved glycan at Asn136 in V1 (T138N mutation) in conjunction with the L494I substitution in C5 within the association site. In culture 2, replication was restored with deletion of the N139INN sequence, which ablates the overlapping Asn141-Asn142-Ser-Ser potential N-linked glycosylation sequons in V1, in conjunction with D601N in the DSR. The 136 and 142 glycan mutations appeared to exert their suppressive effects by altering the dependence of gp120-gp41 interactions on the DSR residues, Leu593, Trp596 and Lys601. The 136 and/or 142 glycan mutations increased the sensitivity of HIV-1 pseudovirions to the glycan-dependent NAbs 2G12 and PG16, and also pooled IgG obtained from HIV-1-infected individuals. Thus adjacent V1 glycans allosterically modulate the distal gp120-gp41 association site. We propose that this represents a mechanism for functional adaptation of the gp120-gp41 association site to an evolving glycan shield in a setting of NAb selection.